AN UNMANNED AERIAL VEHICLE FOR MULTI-PURPOSE TASKS IN CONSTRUCTION INDUSTRY - Cajzek, Rok; Klanšek, Uroš (Journal of Applied Engineering Science, 2016)
The aim of this paper is to present an unmanned aerial vehicle (UAV) developed for multipurpose usage in construction industry such as construction site monitoring, examination of constructions, infrared thermography, photogrammetry, transport applications and also for marketing activities. Initially, this article briefly introduces the possibilities of UAV applications in construction industry. Thereupon, the paper presents the structure, the hardware and the software system of a hexacopter, specially developed as the UAV for multipurpose use at construction sites and on locations of existing facilities. Due to the nature of the movement and vibrations created during the flight, it was necessary to develop a stabilizing system for capturing quality photos and videos. Therefore, this paper also exposes an applicable solution for such stabilization system which was installed in the UAV. Furthermore, some actual practices and applications performed employing the developed UAV in the field are shown at the end of the paper. The possible uses of the developed UAV demonstrated that it is suitably operational for multipurpose tasks, particularly on the account of its flexibility, generated thrust and installed software system. Additionally, it is unlike the out of the box systems, which are usually intended for single use.
Keywords: Image stabilization; Construction Industry; Multitasking; UAV; Unmanned aerial vehicles